Toward a Regional Gerontological Agenda: The Use of Empowerment Evaluation. (January 2022) - Schwartz, Abby J.; Bower, Kyle L.; Rowles, Graham D.; Appert, Karen M.; Ferguson, Lee Ann S.
This article describes the application of an empowerment evaluation approach to nurturing the growth and priority setting of a regional organization. A model is provided of the processes whereby the Southern Gerontological Society (SGS) identified research and service priorities by conducting a survey of stakeholder perceptions of regional needs. The survey goal was to identify important issues faced by older adults in the South as a prelude to refining SGS research and service priorities and developing its contemporary regional gerontological agenda. We trace how the survey findings were translated into actions including shaping the annual meeting program, creating new standing committees, and developing service activities. Underlying the process of developing and refining this agenda are a set of key principles that have come to characterize the operation of SGS. These principles are discussed and provide a model for comparable organizations seeking to develop agendas consistent with their mission and identity.